Ambidextrous Management of Design in the Age of Artificial Intelligence - Driven Digital Innovation: A Narrative Review - Hwangbo, Hyunwook (International Journal of Building, Urban, Interior and Landscape Technology, 2026)
Design is increasingly understood as a sociomaterial practice in which human actors and material agencies co-produce problem solving and meaning in evolving sociotechnical systems. This narrative review synthesizes fragmented work on generativity and generative design and traces how organizational design languages have shifted from control- and governance-oriented approaches toward enabling, open, and collaborative forms of organizing. Drawing on classic cases from Xerox PARC and Frank O. Gehry’s technology enabled architectural practice, and on theories of digital materiality and layered modular architecture (LMA), the paper shows how digital artifacts remain incomplete and recombinable while generative AI amplifies both generative capacity and sociotechnical risk (e.g., overload, homogenization, privacy, and accountability challenges). This paper advances an ambidextrous view of design management for AI-driven digital innovation: organizations should enable generativity while deploying nuanced, human-centered controls - including governance, formalization, and interdisciplinary oversight—to steer evolving design practices toward accountable and ethically defensible outcomes.